2006
DOI: 10.1002/jsfa.2650
|View full text |Cite
|
Sign up to set email alerts
|

The influence of malolactic fermentation and Oenococcus oeni strain on glycosidic aroma precursors and related volatile compounds of red wine

Abstract: Free and glycosidically bound volatile compounds of red wine were measured after malolactic fermentation (MLF) with four different commercial starter cultures of Oenococcus oeni. MLF resulted in a significant decrease in the concentration of total glycosides, expressed as phenol-free glycosyl glucose. Gas chromatographic analyses of wine enzyme hydrolysates showed that the extent of hydrolysis of glycosides during MLF was dependent on both bacterial strain and chemical structure of the substrate. The highest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 25 publications
2
48
2
1
Order By: Relevance
“…The analytical methods most used to investigate correlation between chemical composition of red wines and environmental factors related to winemaking are: High Performance Liquid Chromatography (HPLC) [8], Gas Chromatography-Mass Spectrometry (GC-MS) [9], Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR-MS) [10,11], High Performance Ion Exclusion Chromatography (HPICE) [12], and Nuclear Magnetic Resonance Spectrometry (NMR), used both with classical [12][13][14] and Site Natural Isotopic Fractionation (SNIF) NMR techniques [15].…”
Section: Introductionmentioning
confidence: 99%
“…The analytical methods most used to investigate correlation between chemical composition of red wines and environmental factors related to winemaking are: High Performance Liquid Chromatography (HPLC) [8], Gas Chromatography-Mass Spectrometry (GC-MS) [9], Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR-MS) [10,11], High Performance Ion Exclusion Chromatography (HPICE) [12], and Nuclear Magnetic Resonance Spectrometry (NMR), used both with classical [12][13][14] and Site Natural Isotopic Fractionation (SNIF) NMR techniques [15].…”
Section: Introductionmentioning
confidence: 99%
“…rhamnosidases. Based on their adaptation to the harsh wine milieu and their general hydrolytic abilities toward different glycosides (16,17,50), wine-related lactic acid bacteria (LAB) have attracted much interest as a potential source of novel glycosidases (34).Consequently, several (intracellular) glycosidases from different wine-related bacterial species have already been identified and characterized (11,12,(36)(37)(38)48). Another driving force for the identification and characterization of bacterial glycosidases, including rhamnosidases, is the observation that plant secondary metabolites (i.e., flavonoids) with potential health benefits have improved bioavailability in their aglycon forms (26).…”
mentioning
confidence: 99%
“…rhamnosidases. Based on their adaptation to the harsh wine milieu and their general hydrolytic abilities toward different glycosides (16,17,50), wine-related lactic acid bacteria (LAB) have attracted much interest as a potential source of novel glycosidases (34).…”
mentioning
confidence: 99%
“…It has been reported that the possession of glycosidic activities is widespread and strain dependent among O. oeni strains (Grimaldi et al 2005a;Saguir et al 2009;Michlmayr et al 2012a). Moreover, some authors pointed out that during MLF, the final concentration of glycoside-derived volatile metabolites depended not only on the actual hydrolytic ability of individual strains, but also on the chemical structure of substrate (Boido et al 2002;Ugliano et al 2006). Thus assaying the βG activity with natural aroma precursors was necessary for an adequate evaluation of the glycosidase potential of O. oeni strains (Gagne et al 2011).…”
mentioning
confidence: 99%
“…Thus assaying the βG activity with natural aroma precursors was necessary for an adequate evaluation of the glycosidase potential of O. oeni strains (Gagne et al 2011). Related work of assaying the βG activity of O. oeni strains with natural glycosylated compounds isolated from grapes/wine and oak wood has also been reported (McMahon et al 1999;Mansfield et al 2002;D'Incecco et al 2004;Ugliano et al 2006;Bloem et al 2008;Gagne et al 2011). O. oeni SD-2a and 31MBR are two important strains widely used during winemaking in China.…”
mentioning
confidence: 99%